Fatah Jay Aassay Passay: In the Milieu of Fatah Halepoto - Dawood, Anita; Halepoto, Fatah; Nasar, Hammad; Talpur, Muhammad Ali (Green Cardamom, 2010)
Exhibition catalog. Jun-Jul 2010. Exhibition @ Sindh Museum, Hyderabad; VM Art Gallery, Karachi. Text in Sindhi: Ayaz Jokhio and Aslam Khwaja. 'Published in conjunction with the exhibition "Fatah Jay Aassay Paassay/ In the Milieu of Fatah Halepoto." It features work by Imran Channa, Nizam Dahiri, Fakeero, Ayesha Jatoi, Arif Hussain Khokhar, Ahmed Ali Manganhar and Mohammad Ali Talpur. Curated by Hammad Nasar and Mohammad Ali Talpur, the exhibition explores the influence of Fatah Halepoto, renowned artist, teacher and writer from Sindh, whose teaching influenced a remarkable flourishing of talent from this area in Pakistan.' (Green Cardamom) 'Fatah Jay Aassay Paassay/ In the Milieu of Fatah Halepoto' is held at Sindh Museum, Hyderabad in June 2010 and VM Art Gallery, Karachi in July. Includes artist biographies.
English; Sindhi
Keywords: 21st century; N4390-5098 Visual Arts. Exhibitions; Pakistan -- Sindh